2004
DOI: 10.1074/jbc.m404690200
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Activity Relationships in Defensin Dimers

Abstract: Defensins are cationic antimicrobial peptides that have a characteristic six-cysteine motif and are important components of the innate immune system. We recently described a ␤-defensin-related peptide (Defr1) that had potent antimicrobial activity despite having only five cysteines. Here we report a relationship between the structure and activity of Defr1 through a comparative study with its six cysteine-containing analogue (Defr1 Y5C). Against a panel of pathogens, we found that oxidized Defr1 had significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(40 citation statements)
references
References 38 publications
1
38
1
Order By: Relevance
“…Thus, the structural framework of ␤-defensin molecules appears to tolerate a substantial variability of amino acid sequences and is also robust to the environmental changes (for instance, pH of crystallization conditions varies between 4.6 and 8.5). This observation is consistent with the existence of many proteins adopting a defensin-like fold despite rather low amino acid sequence homology (52). Consistent with previous results of studies in solution (44,45), formation of distinct oligomers of hBD1 was not observed for any of the 10 structures.…”
Section: Discussionsupporting
confidence: 81%
“…Thus, the structural framework of ␤-defensin molecules appears to tolerate a substantial variability of amino acid sequences and is also robust to the environmental changes (for instance, pH of crystallization conditions varies between 4.6 and 8.5). This observation is consistent with the existence of many proteins adopting a defensin-like fold despite rather low amino acid sequence homology (52). Consistent with previous results of studies in solution (44,45), formation of distinct oligomers of hBD1 was not observed for any of the 10 structures.…”
Section: Discussionsupporting
confidence: 81%
“…It is plausible that the conserved salt bridge affords these ␣-defensins proteolytic resistance to their processing enzymes. In fact, Ouellette and colleagues (56) demonstrated that structural stability afforded by disulfide bonding in mouse ␣-defensins (cryptdins), whereas not required for their antimicrobial function as shown in several ␤-defensins (28,58,59), is essential for preventing in vivo proteolytic degradation by their processing enzyme, the metalloproteinase matrilysin (38,60). Our work has established the importance of two highly conserved, oppositely charged residues in maintaining ␣-defensin in vivo stability and thus biological functions of these multifaceted immunological molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Defb14, Defb14-1c v , and HBD3 were obtained from Chemical Synthesis Services-Albachem Ltd. (Gladsmuir, UK). Disulfide connectivities were determined by proteolysis and peptide mass mapping as previously published (10,20). Briefly, a 50 M solution of the peptide was subjected to proteolytic cleavage with a combination of trypsin and chymotrypsin (Sigma) for HBD3.…”
Section: Methodsmentioning
confidence: 99%
“…Antimicrobial Assays-These assays were carried out as previously described (20). Briefly, test organisms were grown to midlogarithmic phase in Iso-Sensitest broth (Oxoid) growth medium and then diluted to 1-5 ϫ 10 6 colony-forming units/ml in 10 mM potassium phosphate containing 1% (v/v) Iso-Sensitest broth, pH 7.4.…”
Section: H Nmr Spectroscopy-one-dimensionalmentioning
confidence: 99%
See 1 more Smart Citation